Midazolam and triazolam in out-patients: A double-blind comparison of hypnotic efficacy - Costa E Silva, J.A. (1983)
1 The hypnotic efficacy and the effect on the condition after morning awakening of midazolam 15 mg and of triazolam 0.5 mg were studied in a multicentre, double-blind cross-over study in 198 out-patients with sleeping difficulties of various origin. 2 The subjects received each drug for two consecutive nights, and completed a questionnaire each day on awakening. 3 Both midazolam and triazolam significantly shortened the sleep-onset latency, reduced the number of awakenings, and increased the total sleep time. 4 The state on awakening was also significantly improved after both compounds for several self-rated items. There was a difference only with regard to the patients' feeling of being under drug influence, which was reported as being significantly more marked after triazolam. 5 In conclusion, both compounds were effective and well tolerated in the doses used, only a few side-effects being reported.